Community mobility plans for individuals with developmental disabilities: A feasibility study. (May 2020) - Pfeiffer, Beth; Falo, Katelyn; Gallagher, Laura; Kaufmann, Christine; Li, Jennie; Yabor, Felicia
Introduction: Individuals with intellectual and/or developmental disabilities have unmet transportation needs, which limits their community mobility. Access to transportation is linked to community participation and independence in adult outcomes. The purpose of this study is to examine the implementation feasibility of individualized community mobility plans. Methods: A pre-test post-test one group design was used to determine if methodology and implementation procedures were feasible. Outcome measures were evaluated to determine if appropriate for future effectiveness research. Participants were six adults with intellectual and/or developmental disabilities who received the community mobility plans intervention over a period of 3–8 sessions. Community mobility plans use a cyclical process where the individual first develops self-determined community mobility goals, followed by a comprehensive assessment process, and individualized environmental and person-centered travel interventions. Results: Participants demonstrated significant improvement between pre- and post-test scores on the measures of the Progressive Evaluation of Travel Skills ( t (5) = –4.481, p = .007) and Goal Attainment Scaling ( t (5) = –7.457, p =.001). Conclusion: Community mobility plans may provide a feasible option to improve community mobility for individuals with intellectual and/or developmental disabilities, although further research is needed to determine effectiveness.